PERAN SARKOPENIA SEBAGAI FAKTOR RISKO GANGGUAN VISUOSPASIAL PADA LANSIA - Wong, Brian (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Visuospatial impairment, as a form of cognitive impairment, could serve as an early indication of dementia in the elderly. Sarcopenia, a progressive and generalized skeletal muscle disorder, can be associated with the risk of visuospatial impairment in the elderly. Aim: This study aims to get an overview of visuospatial impairment with its associated risk factors in the elderly at Pusaka Kebon Jeruk, West Jakarta. Methods: This study uses a cross-sectional involving 100 respondents aged 60 years and above. Visuospatial impairment is measured using constructional praxis. An elder is considered to has visuospatial impairment if scoring < 11. Sarcopenia is assessed according to European Working Group on Sarcopenia in Older People 2 (EWGSOP2). Frailty status is evaluated using the Fried frailty phenotype. Blood glucose and serum cholesterol levels are measured through laboratory tests. Results: This study included 100 respondents, with 50 respondents having visuospatial impairment. Bivariate analysis found a significant association between sarcopenia and visuospatial impairment (P: 0.016, OR: 2.667, 95% CI: 1.188 Ã¢â‚¬â€œ 5.985). Multivariate analysis found a similar result, that is a significant association between sarcopenia and visuospatial impairment (P: 0.017, OR: 2.752, 95% CI: 1.203 Ã¢â‚¬â€œ 6.296). Bivariate analysis was done by using Ãâ€¡2 test, while multivariate analysis was done by using binary logistic regression using backward analysis. Discussion: Sarcopenia is significantly associated with visuospatial impairment, increasing the risk of visuospatial impairment by 2.752-fold. Keywords: Elderly, Sarcopenia, Visuospatial impairment,